The Influence Of Christian Leadership Strategy And Financial Management On The Effectiveness Of Church Ministry In GMIM Tomohon Tiga Region - Mandey, Aldie Haris; Wuwung, Olivia Cherly; Weol, Wolter (International Journal of Education, Information Technology, and Others, 2025)
This study investigates the influence of Christian leadership strategies and financial management on the effectiveness of church ministry in GMIM Tomohon Tiga Region. Utilizing a quantitative associative approach with a survey method, the study analyzed data from church leaders and members across multiple congregations. Findings revealed that Christian leadership strategy has a significant positive effect on ministry effectiveness (p < 0.05), as does financial management. Simultaneously, both factors strongly predict ministry effectiveness, with R² = 0.979, indicating that 97.9% of variations in ministry effectiveness are explained by these variables. These results suggest that strengthening spiritual leadership and implementing professional financial management practices are crucial for enhancing the quality and impact of church ministry. Keywords: Christian leadership strategy, financial management, ministry effectiveness.